Aerobic fitness moderates girls' affective and working memory responses to social exclusion. (July 2021) - Delli Paoli, Anthony G.; Smith, Alan L.; Pontifex, Matthew B.; Moser, Jason S.
Abstract: Because self-regulation skills are in development through adolescence, social exclusion can pose significant challenges to the well-being of young people. Thus, an understanding of factors that may ease the self-regulation demands of social exclusion is particularly important. One such factor is aerobic fitness. Using a quasi-experimental within-subject design in a sample of girls ( N  = 47, 10.4 ± 1.2 years), we examined whether affective and working memory changes following social exclusion differ by level of aerobic fitness. Overall, findings suggest that more aerobically fit girls may better regulate the demands of social exclusion than less aerobically fit girls. Specifically, girls with higher aerobic fitness evidenced smaller decreases in pleasant affect and larger increases in working memory performance following social exclusion than girls with lower aerobic fitness. This research extends understanding of how aerobic fitness may benefit well-being in young people. Highlights: Aerobic fitness may reduce affective responses to social exclusion in girls. Aerobic fitness may help regulate the cognitive demands of social exclusion. Aerobic fitness may help girls be resilient within challenging social settings.